2017
DOI: 10.1530/rep-17-0054
|View full text |Cite
|
Sign up to set email alerts
|

Oviduct extracellular vesicles protein content and their role during oviduct–embryo cross-talk

Abstract: Successful pregnancy requires an appropriate communication between the mother and the embryo. Recently, exosomes and microvesicles, both membrane-bound extracellular vesicles (EVs) present in the oviduct fluid have been proposed as key modulators of this unique cross-talk. However, little is known about their content and their role during oviduct-embryo dialog. Given the known differences in secretions by and oviduct epithelial cells (OEC), we aimed at deciphering the oviduct EVs protein content from both sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
290
2
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(322 citation statements)
references
References 65 publications
24
290
2
6
Order By: Relevance
“…Notably, oviduct fluid‐derived EVs decreased ROS, 5‐mC, DNMT1, and DNMT3a levels and increased the blastocyst rate of embryos in the in vitro experiments. This is in line with a previous study where EVs derived from bovine oviduct fluid were found crucial to fertilization and early‐stage embryonic development . Moreover, this beneficial effect of EVs was attenuated by luzindole in our study, indicating a positive association between melatonin and EVs on ROS and 5‐mC levels.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Notably, oviduct fluid‐derived EVs decreased ROS, 5‐mC, DNMT1, and DNMT3a levels and increased the blastocyst rate of embryos in the in vitro experiments. This is in line with a previous study where EVs derived from bovine oviduct fluid were found crucial to fertilization and early‐stage embryonic development . Moreover, this beneficial effect of EVs was attenuated by luzindole in our study, indicating a positive association between melatonin and EVs on ROS and 5‐mC levels.…”
Section: Discussionsupporting
confidence: 93%
“…EVs consist of lipids, proteins, RNA, and other components . EV lipidomic studies characterized EV lipid species from reticulocytes, B lymphocytes, mast cells, dendritic cells, and prostate cancer cells, and approximately 280 molecular lipid species were characterized from prostate cancer cellline‐derived EVs, while 319 proteins were identified in EVs, some of which may bind to melatonin, such as albumin, and pepsin . Melatonin can interact with hydrophobic sites due to its lipid solubility .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The consequences of such differences are not known, but it is worth noting that EV from ampulla may be involved in the fine tuning sperm performance in the proximity of the egg. Consistently, oviductal EV may also modulate embryo physiology …”
Section: Discussionmentioning
confidence: 88%
“…Interestingly, our data showed that EVs derived from outgrowth have unidentified proteins and genetic materials, and it also proved EVs are known to transfer various biomolecules, including proteins, lipids, mRNAs, and miRNAs (Thery et al, ). Alminana et al () reported that coincubation with bovine oviduct EVs improved blastocyst rates, hatching ability, and blastomere count of the blastocyst. Protein contents in oviduct EVs cargo may influence embryonic development and quality by activation of gamete interaction.…”
Section: Discussionmentioning
confidence: 99%